Upaya Mengatasi Masalah Membuat Sarana Sembahyang dengan Metode Tutor Sebaya Secara Kulon (Kutu Loncat) di Kelas III A SD Negeri 11 Cakranegara - Maytriana, Ida Ayu Yesi (Lembaga Yasin AlSys, 2022)
This classroom action research was motivated by the low value of Hinduism in class III A students. This study aims to improve the learning outcomes of Hinduism in class IIIA, especially the material for prayer facilities using the Kulon peer tutoring method (Kutu Skip). This research was conducted from August to October 2018 for the 2018/2019 academic year or semester I, taking place in class III A SDN 11 Cakranegara. This type of research is Classroom Action Research with two cycles consisting of three meetings in one cycle, each cycle consisting of: planning, implementing, observing and reflecting. Data collection techniques and tools in this study used data analysis techniques in the form of student work documents, score lists and observation sheets. The results showed that with the Kulon peer tutoring method (Kutu Skip) there was a pleasant learning atmosphere so that student learning outcomes increased, namely from the results of cycle I to Cycle II there was an increase, in cycle 1 the number of students who received a complete score was 14 students or 46 .67%, the incomplete score in cycle 1 was 16 students or 53.33%, while in cycle 2 there was an increase in the completeness score to 26 students or 86.67% an increase of 40%. It was concluded that the Kulon (Kutu Skip) peer tutoring method can improve the learning outcomes of Hinduism, especially the prayer facilities material.